Effect of carnichrome® on growth performance of weanling pigs in a commercial environment - N Z Frantz; J C Woodworth; Jim L Nelssen; Joel M DeRouchey; Robert D Goodband; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
A 43-day growth study with a total of 384 weanling pigs (14 ± 2 d of age) was conducted to evaluate the effects of CarnichromeÂ®, a combination of L-carnitine and chromium picolinate, on growth performance of weanling pigs. Secondary objectives were to compare pigs fed diets with or without a feed-grade medication, evaluate any interactive effects between Carnichrome and medication, and identify any carryover effect once medication was withdrawn from the diet. Experimental diets were arranged in a 2 × 3 factorial to compare the main effects of medication (none or Denagard/CTC, 35/400 g/ton) and Carnichrome (none, 25, and 100, or 50 and 100 ppm, respectively, of L-carnitine and chromium picolinate). No interactions between Carnichrome and Denagard/CTC were detected (P>0.17). Pigs fed Denagard/ CTC had improved ADG (P0.14), and no carryover effect of medication resulted. Pigs fed nursery diets containing Carnichrome did not have enhanced growth performance, but pigs fed diets containing Denagard/CTC had improved ADG, ADFI, and F/G compared with those of pigs fed diets without Denagard/CTC.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Swine; Antibiotics; L-carnitine; Chromium; Pigs; Weanling pigs